Detection of Antimicrobial Resistance in Bacterial Pathogens from the Aquatic Environment at Selected Sites in Panangad Region - Hemanta, Pokhrel (School of Aquaculture and Biotechnology, 2015)
Abstract- Resistance to antimicrobial agents among clinically important pathogens in the community and environment has compromised therapy and requires constant monitoring of emerging pathogens. Current investigation was aimed at determining the antimicrobial resistance pattern in bacteria isolated from public water body near a hospital where fishing is carried out and also from two fish farms which used the same water for aquaculture. Bacterial strains were isolated from water, soil and fish of the three stations within the study area. Of 105 isolates, maximum number of isolates belonged to the Enterobacter spp. Antibiotic sensitivity tests showed that most of the isolates had high level of resistance against commonly used antibiotics. Multiple antibiotic resistance (MAR), i.e. resistance to more than two antibiotics, occurred in almost 100% of Enterobacter spp. and Streptococcus spp. Antibiotic resistance index (ARI) and MAR index were calculated for the isolates. Most strains exhibited multi drug resistant character and all the isolates had a very high multiple antibiotic-resistance index, suggesting the origin of the isolates is from an area highly contaminated with antibiotics. Antibiotic resistance indices were found to be highest for Enterobacter spp. followed by Streptococcus spp and lowest for Vibrio and Aeromonas group. Methicillin and vancomycin resistance genes were detected in strains resistant to methicillin and vancomycin, isolated from the study area. Study of the mutation frequency revealed that longer duration of exposure to antibiotics is a sufficient cause for bacteria to mutate and acquire resistance. A major mechanism of transfer of AMR was found to be plasmid mediated. This is the first report of the occurrence of clinical isolates such as Klebsiella pneumonia and Klebsiella oxytoca with multi drug resistance in aquatic environment including in fish, suggesting the rapid spread of isolates and AMR genes between environments. The study revealed that imprudent use of antibiotics in hospital and release of the waste without prior treatment may have led to the dissemination of resistance from terrestrial to aquatic organism.